The extended pterional approach allows excellent results for removal of anterior cranial fossa meningiomas - Jose Carlos Lynch; Mariangela Barbi Gonçalves; Celestino Esteves Pereira; Wladimir Melo; Gianni Ferraz Temponi (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To describe a unique operative strategy, instead the classical pterional approach, and to analyses it safety and effectiveness for removal of anterior cranial fossa meningiomas. Method We identify 38 patients with tuberculum sellae and olphactory groove meningiomas operated between 1986 and 2013. Medical charts, operative reports, imaging studies and clinical follow-up evaluations were reviewed and analyzed retrospectively. The pterional craniotomy is extended toward the frontal bone providing access through the subfrontal route, besides the usual anterolateral view provided by the classical pterional approach. Results Surgical mortality occurred in one patient (2.6%). Gross total resection was achieved in 27 patients (86.8%). Median time of follow-up was 69.4 months. Conclusion The extended pterional approach allows excellent results. Total removal of meningiomas of the anterior cranial fossa was obtained in 86.8 % of patients, with low morbidity and mortality.